Extraversion and emotional expressiveness: Moderators of the relationship between curmudgeon personality and workplace incivility. (October 2022) - Islam, Md Rashedul; Bowling, Nathan
Abstract: Curmudgeon personality, which is the tendency to dislike various attitude objects, has been linked to several important criteria, including specific attitudes (e.g., consumer satisfaction), subjective well-being, and physical health. We extend this research by examining curmudgeon personality's relationship with an important interpersonal variable: exposure to workplace incivility. Drawing from the provocative victim perspective, we argue that workers who are high in curmudgeon personality may be disproportionately exposed to workplace incivility—primarily because their unpleasant nature provokes their coworkers and supervisors to target them with uncivil behaviors. Such effects, however, may only be present among curmudgeons who voice their discontent. We thus predicted that extraversion and emotional expressiveness, both of which reflect one's tendency to express themselves to others, would moderate the curmudgeon personality-workplace incivility relationship. Specifically, we expected the curmudgeon personality-incivility relationship to be stronger among workers who are high in extraversion (emotional expressiveness) than among workers who are low in extraversion (emotional expressiveness). Data from an employee sample ( N = 389) provided support for these moderator effects. Our findings thus extend scientific understanding of the hypothesized effects of curmudgeon personality, and they contribute to the literatures on victim provocation and trait × trait interaction. Highlights: Curmudgeon personality and workplace incivility: Victims may provoke perpetrators. Curmudgeon personality with higher level of extraversion is more active. Curmudgeon personality with higher level of emotional expressiveness is more active. Curmudgeons high in extraversion experience more workplace incivility. Curmudgeons high in emotional expressiveness experience more workplace incivility.